Tinjauan Teologis Merespons Series Film In The Name Of God: A Holy Betrayal: Anti-Kristus Berdasarkan 2 Yohanes 1:7-11 - Hia, Lurusman Jaya; Wijaya, Hendi (Sekolah Tinggi Teologi Aletheia, 2024)
Abstract:Antichrist is a deceiver who is very close to Christians, so as Christians, it is important to criticise those who play God based on the Christian faith through the Book of 2 John 1:7-11. The purpose of the study is to respond to the four sects that play God promising salvation for believers in the film In The Name Of God: A Holy Betrayal. This study uses the research method of exegesis study with the meaning of the four layers of the Bible namely Historia (Sarkic), Theoria (Noetic), Moral (Psychic), Anagogic and film analysis approach. Through this study, it can be concluded that the film In the Name of God: A Holy Betrayal has become part of the Antichrist. Thus the church needs to be vigilant and fight against those who are against God by rejecting them to be able to contribute to the impact of society and truly live as believers in Jesus Christ. AbstrakAntikristus adalah penyesat yang sangat dekat dengan orang Kristen, sehingga sebagai orang Kristen mengangkat kritik terhadap oknum-oknum yang playing God menjadi penting untuk dilakukan berdasarkan iman Kristen melalui Kitab 2 Yohanes 1:7-11. Tujuan dari penelitian adalah untuk menanggapi empat sekte yang berperan sebagai Tuhan yang menjanjikan keselamatan bagi orang percaya dalam film In The Name Of God: A Holy Betrayal. Kajian ini menggunakan metode penelitian studi eksegesis dengan makna empat lapisan Alkitab yakni Historia (Sarkic), Theoria (Noetic), Moral (Psychic), Anagogic dan pendekatan analisis film. Melalui kajian ini dapat disimpulkan bahwa film In the Name of God: A Holy Betrayal telah menjadi bagian dari antikristus. Dengan demikian gereja perlu waspada dan melawan oknum-oknum yang melawan Allah dengan menolak mereka untuk dapat berkontribusi memberikan dampak bagi masyarakat dan benar-benar hidup sebagai orang percaya kepada Yesus Kristus.